DNA sequences in the rat osteocalcin gene that bind the 1,25-dihydroxyvitamin D3 receptor and confer responsiveness to 1,25-dihydroxyvitamin D3. - Demay, M B (1990)
The 5' flanking region of the rat osteocalcin gene has been shown to confer responsiveness to 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] after transfection of fusion genes into ROS 17/2.8 cells. Deletion analysis has demonstrated that there are at least two domains in this 5' flanking region that contribute to 1,25(OH)2D3 responsiveness; however, only the downstream region is able to confer 1,25(OH)2D3 responsiveness to either the native osteocalcin promoter or to a heterologous viral promoter (herpes simplex virus thymidine kinase). The proximal region responsible for 1,25(OH)2D3 induction of the rat osteocalcin gene lies 458 base pairs upstream from the transcription start site of this gene. A 25-base-pair oligonucleotide corresponding to the sequences in this region is able to confer 1,25(OH)2D3 responsiveness to the thymidine kinase promoter in an orientation-independent fashion. This sequence contains three copies of a short sequence that are homologous to "half-sites" of steroid response elements. Gel-retardation assays using porcine intestinal nuclear extract as a rich source of 1,25(OH)2D3 receptor demonstrated retardation in the migration of probes containing the sequence noted above. A monoclonal antibody directed against the 1,25(OH)2D3 receptor caused further retardation in the migration of these protein-DNA complexes. Therefore, the sequences represented in this oligonucleotide encompass the sequences necessary for binding of the 1,25(OH)2D3 receptor to DNA as well as those sequences necessary for 1,25(OH)2D3 to induce osteocalcin gene transcription.